Application Of Three-Dimensional Reconstruction For Planning Complex Surgical Interventions In Newborns - Trifonova, Maria Maksimovna; Mukailova, Liana Magomedovna; Durdyev, Yazmyrat; Bogatyreva, Karina Eduardovna; Gadzhiyasulaeva, Albina Zalimkhanovna; Arsanalieva, Saniyat Mikailovna; Farzieva Bafta Samеd kyzy (Journal of Neonatal Surgery, 2025)
In modern medicine three-dimensional reconstruction methods are more and more widely used in various fields of surgery. They are of particular relevance when planning and performing complex surgical interventions in newborns, since any error in the preoperative assessment of anatomical structures can affect the outcome of treatment. This study analyses the possibilities of three-dimensional reconstruction in planning operations for congenital malformations and evaluates the effectiveness of this approach in improving diagnostic accuracy and reducing surgical time.